Caught between Roosevelt & Stalin : America's ambassadors to Moscow - Dunn, Dennis J. (University Press of Kentucky, 1998)
On November 16, 1933, Franklin D. Roosevelt and Soviet Commissar of Foreign Affairs Maxim Litvinov signed an agreement establishing diplomatic ties between the United States and the Soviet Union. Two days later Roosevelt named the first of five ambassadors he would place in Moscow between 1933 and 1945. Caught between Roosevelt and Stalin tells the dramatic and important story of these ambassadors and their often contentious relationships with the two most powerful men in the world. More than fifty years after his death, Roosevelt's foreign policy, especially regarding the Soviet Union, remains a subject of intense debate. Dennis Dunn offers an ambitious new appraisal of the apparent confusion and contradiction in Roosevelt's policy - one moment publicizing the four freedoms and the Atlantic Charter and the next moment giving tacit approval to Stalin's control of parts of Eastern Europe and northeast Asia. Dunn argues that "Rooseveltism," the president's belief that the Soviet Union and the United States were both developing into modern social democracies, blinded Roosevelt to the true nature of Stalin's brutal dictatorship despite repeated warnings from his ambassadors in Moscow